Perceptions of postgraduate family medicine supervision at decentralised training sites, South Africa - Neetha J. Erumeda; Louis S. Jenkins; Ann Z. George (AOSIS, 2022)
Background: Specialist training in family medicine (FM) is growing rapidly in sub-Saharan Africa. The strong emphasis on workplace-based learning for speciality training makes it vital to gain in-depth insights into registrar supervision. Previous studies have explored aspects of supervision at decentralised sites in high-income countries, however, little is known about the benefits and constraints of decentralised postgraduate supervision in low- to middle-income countries, especially in Africa. Aim: This study aimed to explore family physicians' and registrars' perceptions of the strengths and challenges of clinical and educational supervision across decentralised training sites. Setting: The study was conducted across two provinces at five decentralised training sites affiliated with the University of the Witwatersrand, Johannesburg. Methods: This qualitative study involved semi-structured interviews with a purposive sample of 11 FPs and 11 registrars. The data were thematically analysed. Results: Two of the four themes identified, 'supervision is context-specific and supervisor-dependent', and 'the nature of engagement matters', involved strengths and challenges. The other two, 'supervision is not ideal' and 'the training environment is challenging', focussed on challenges. Conclusion: Supervisors and registrars described the postgraduate FM supervision as context-specific and supervisor-dependent. Supervisors displayed good clinical-teacher characteristics and supervisory relationships. However, several challenges, including registrars' workload, resource shortages and a lack of standardisation across training sites, need to be addressed. Regular faculty development is essential for supervisors to be aware of relevant aspects of, and current trends in, postgraduate training.